Contribuição e equalização de estados de carga de baterias e ao compartilhamento de potência em microrredes CC - Beck, Marlon Felipe (2024)
This dissertation presents the development of a decentralized control and management framework for a direct current (DC) microgrid with two DC-DC converters, proportional-integral (PI) controllers, and an equalization function referred to as k-sliding. The main objectives are energy management and state-of-charge equalization. The equalization function ensures uniform charging and discharging of energy storage elements. Through the adjustment of these functions, the study aims to enhance the overall performance and longevity of the microgrid, maximizing the utilization of energy storage and mitigating issues such as cell degradation. The k-sliding function, designed to equalize the battery state of charge, allows operation with a prioritized system for restoring the DC link voltage or equalization, providing flexibility and efficiency to the microgrid.